The proposal of realization the OGC geospatial web services' symbolization - Olejarz, Grzegorz (My University, 2011)
In the mining industry there is a lack of good standards of creating the mining maps. Such documents are usually issued by non-free software for commercial purposes. Main aim of this article is to analyze the possibilities free and open standards for style spatial data, in according to Polish law and norms. Achieving this goal was possible because of system using Web Services, also based on open software and standards. This article presents installation and configuration of a geospatial service system based on free and open source software: GeoServer, PostGIS and OpenLayers. The sample vector mine data were converted and saved in the spatial database PostGIS and then they were published by using geodata server GeoServer as Web Map Service. Next there were created the portrayal styles of the mining maps elements. The main aim was the adaptation to Polish PKN norms: Mapy górnicze. Umowne znaki granic (Mining maps. Conventional symbols of borders) and Umowne znaki podziemnych wyrobisk górniczych (Conventional symbols of underground excavations). For these styles there were used SLD and SVG OGC standards. Last step was connected with creation of geospatial web services client using OpenLayers. It allowed to display maps just in web browser.

W pracy przedstawiono instalację i konfigurację systemu usług geoprzestrzennych opartych na oprogramowaniu typu open source: GeoServer, PostGIS oraz OpenLayers. Pozyskane przykładowe wektorowe dane kartograficzne mapy wyrobisk górniczych zostały skonwertowane oraz zapisane w przestrzennej bazie danych PostGIS, a następnie za pomocą serwera danych przestrzennych GeoServer zostały udostępnione w postaci usługi WMS. W kolejnym etapie stworzono style wyświetlania poszczególnych elementów mapy górniczej w celu dostosowania ich do norm górniczych PKN: Mapy górnicze. Umowne znaki granic oraz Umowne znaki podziemnych wyrobisk górniczych. Wykorzystano do tego standardy SLD oraz SVG, które posłużyły do resymbolizacji kartograficznej. Ostatnim krokiem było opracowanie klienta usług geoprzestrzennych przy użyciu biblioteki OpenLayers, który umożliwił wyświetlenie mapy w środowisku przeglądarki internetowej.
Propozycja realizacji symbolizacji w serwisach usług geoprzestrzennych OGC
Geomatics and Environmental Engineering
Keywords: OGC Web services; INSPIRE; spatial data infrastructure; SDI; databases; WMS; OGC Web services; styled layer descriptor; INSPIRE; SDI; SLD; bazy danych przestrzennych; WMS; GeoServer; styled layer descriptor; SLD; OpenLayers; GeoServer; OpenLayers; PostGIS; PostGIS